AIDS in Brazilian Journalism: A study of the sources of information in the newspapers Folha de S. Paulo and O Globo - Benetti, Marcia; Darde, Vicente (Brazilian journalism research, 2006)
Journalism, understood as a meaning builder of reality, is a discourse that should represent the diversity of thoughts in a society. This article shows part of the results of a research in which we sought to answer whether Brazilian reference newspapers O Globo and Folha de S. Paulo treat the plurality of social voices talking about Aids in a balanced way. Through Content and Discourse Analysis, we mapped out the themes addressed and the sources of information by analyzing 310 journalistic texts, which represented the total published in both newspapers in 2004. The enunciator concept allowed us to verify that the dominant voices, even though they reﬂected oﬃcial sources, demanded governmental actions in the ﬁght against Aids. We recorded the comparison of enunciators in the texts, which characterized a polyphonic discourse. However, the voices of those living with HIV/Aids were hardly present; thus showing that the ﬁeld of journalism failed to accomplish its function of representing the plurality of social voices.